Challenges in Pediatric Orthodontics and Radiology: Evidence from Recent Studies and Implications for Clinical Practice: A Review Article - Nakhaei, Yasaman; Farahmand, Faranak; Yazdanpanah, Mohammad Hossein; Saeidi Tehran, Nastaran; Ghaffarzade, Seied Kaveh; Soleimani, Sahar; Haji Abbas Oghli, Farnaz (Galen Medical Journal, 2024)
This narrative review delves into the complex challenges inherent in pediatric orthodontics and radiology, fields pivotal to the early detection, prevention, and management of dental and craniofacial developmental issues in children. Pediatric orthodontics plays a critical role as the first line of defense against malocclusions and jaw discrepancies, aiming to establish a foundation for functional, aesthetic, and lifelong oral health. Concurrently, pediatric radiology provides indispensable insights for accurate diagnosis and effective treatment monitoring, yet it raises significant ethical and safety concerns due to the sensitivity of young patients to ionizing radiation. The review highlights several core challenges: managing patient compliance in long-term orthodontic treatment, navigating the technical and ethical complexities of pediatric radiological practices, and addressing socioeconomic barriers that restrict access to necessary care. It emphasizes the need for innovative approaches in treatment and imaging techniques, such as the development and implementation of low-dose imaging protocols and non-ionizing imaging alternatives like ultrasonography and MRI, which aim to reduce the risks associated with radiation exposure.. The review concludes with a call for a judicious approach to imaging and treatment, advocating for policies that enhance accessibility to orthodontic care and radiological services, particularly for underprivileged populations. The integration of innovative technologies, coupled with a focus on preventive care and early intervention, holds the potential to significantly improve outcomes in pediatric orthodontics and radiology, ensuring better long-term oral and craniofacial health for children. This narrative review serves as a comprehensive examination of the current challenges and emerging solutions in pediatric orthodontics and radiology, emphasizing the need for ongoing research and collaboration to advance patient care and treatment methodologies in these crucial fields.